Statistical Detection of the He ii Transverse Proximity Effect: Evidence for Sustained Quasar Activity for >25 Million Years - Schmidt, Tobias M.; Worseck, Gabor; Hennawi, Joseph F.; Prochaska, J. Xavier; Crighton, Neil H. M.; Lukić, Zarija; Oñorbe, Jose (Frontiers in Astronomy and Space Sciences, 2017)
The reionization of helium at z~3 is the final phase transition of the intergalactic medium and supposed to be driven purely by quasars. The HeII transverse proximity effect - enhanced HeII transmission in a background sightline caused by the ionizing radiation of a foreground quasar - therefore offers a unique opportunity to probe the morphology of HeII reionization and to investigate the emission properties of quasars, e.g. ionizing emissivity, lifetime and beaming geometry. We use the most-recent HST/COS far-UV dataset of 22 HeII absorption spectra and conduct our own dedicated optical spectroscopic survey to find foreground quasars around these HeII sightlines. Based on a set of 66 foreground quasars, we perform the first statistical analysis of the HeII transverse proximity effect. Despite a large object-to-object variance, our stacking analysis reveals an excess in the average HeII transmission near the foreground quasars at 3 sigma significance. This statistical evidence for the transverse proximity effect is corroborated by a clear dependence of the signal strength on the inferred HeII ionization rate at the background sightline. Our detection places, based on the transverse light crossing time, a geometrical limit on the quasar lifetime of t_Q > 25 Myr. This evidence for sustained activity of luminous quasars is relevant for the morphology of HI and HeII reionization and helps to constrain AGN triggering mechanisms, accretion physics and models of black hole mass assembly. We show how future modeling of the transverse proximity effect can additionally constrain quasar emission geometries and e.g. clarify if the large observed object-to-object variance can be explained by current models of quasar obscuration.